Thrombomodulin-mediated catabolism of protein C by pleural mesothelial and vascular endothelial cells - Iakhiaev, Alexei V.; Rezaie, Alireza R.; Idell, Steven (Thrombosis and Haemostasis, 2007)
Pleural mesothelial and vascular endothelial cells express protein C (PC) pathway components including thrombomodulin (TM) and endothelial protein C receptor (EPCR) and activate PC by the thrombin-TM dependent mechanism.We used these cells as model systems to identify molecules involved in endocytosis and degradation of PC. We find that mesothelial and endothelial cells can bind, internalize and degrade PC.Addition of thrombin markedly induced degradation of PC by these cells in a TM-dependent fashion, implicating the involvement of the thrombin-TM complex in internalization and degradation of PC. This observation defines a novel function for the thrombin-TM complex as a degradation receptor for PC and suggests that PC is degraded concurrent with its activation.A PC Gla-domain mutant, which is unable to bind to the EPCR, was degraded by the cells to a lesser extent than wild-type PC, implicating the PC degradation concurrent with its activation. Consistent with the role of thrombin-TM complex as a degradation receptor, the catalytically inactive thrombin-S195A also induced PC degradation though to a lesser extent than wild-type thrombin.This suggests that generation of activated PC (APC) can contribute to accumulation of degradation products, but is not essential for the thrombin-induced degradation of PC. The thrombin-TMmediated degradation of PC by both cell types suggest a previously unrecognized mechanism, which can contribute to PC consumption.This mechanism may be pathophysiologically relevant and can contribute to an acquired PC deficiency in conditions characterized by sustained thrombin generation.
Keywords: Endocytosis; proteases; protein C/S pathway; thrombin; thrombomodulin